KONSEP KHAUF DALAM TAFSIR AL - MISBAH Telaah Atas Pokok-Pokok Pikiran Tasawuf M. Quraish Shihab - Ikrar Ikrar (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
Khauf is a concept that usually exists in Tasawwuf. Khauf is usually coupled with rajâ'. Khauf and rajâ’ ‘are two concepts that describe God's relationship with humans. On the one hand, humans are afraid of God, but on the other hand humans have no place of hope other than Allah. On the one hand, humans are afraid of the effects of their sins that are not forgiven by God, but on the other hand humans have no place to beg forgiveness except to God. God is feared as well as expected. This study traces the meaning of khauf in the Al-Quran, especially the meaning of khauf according to M. Quraish Shihab in his work, Tafsir Al-Mishbah. This study found the typical way of M. Qu- raish Shihab in interpreting the Al-Quran, namely connecting the word khauf with the context of the sentence or verse where the word khauf was mentioned. One important finding of this study is that according to M. Quraish Shihab, the word khauf in the Al-Quran is always coup- led with the word rabb. Rabb means keeper or educator. Therefore, M. Quraish Shihab emphasized that the meaning of khauf must not be separated from the meaning of rabb or the fear of humans to God must be within the framework of God›s care and education of humans